INCREASING LECTURER PRODUCTIVITY THROUGH THE REINFORCEMENT OF ACHIEVEMENT NEEDS, ORGANIZATIONAL CULTURE, WORK ETHIC, WORK MOTIVATION AND COMPENSATION:: Empirical Study using Path Analysis and SITOREM Analysis on Lecturers of Universitas Muhammadiyah Tangerang - Achmad Fauzi; Soewarto Hardhienata; Oding Sunardi; Ahmad Arif Fadilah; Solihin Solihin (JF Publisher, 2024)
This research aims to identify ways to increase the productivity of lecturers at Universitas Muhammadiyah Tangerang through strengthening achievement needs, organizational culture, work ethic, work motivation, and compensation by using path analysis and SITOREM analysis methods. The research sample consisted of 215 lecturers from a population of 464 lecturers, which were selected through proportional random sampling. Findings indicated a direct positive significant influence of achievement needs (β=0.189), organizational culture (β=0.322), and work motivation (β=0.155) on lecturer productivity, while work ethic (β=0.170) and compensation (β=0.133) had no significant influence. There is also a significant direct influence of achievement needs, organizational culture, and work ethic on work motivation and compensation. In addition, a significant indirect influence of achievement needs and organizational culture on productivity through work motivation and compensation was identified, while work ethic had no significant indirect influence. This research tested 17 hypotheses, with 11 hypotheses testing direct influence and 6 hypotheses testing indirect influence.